PEMBELAJARAN TEKS ANEKDOT KURIKULUM 2013 KELAS X SMA KEMALA BHAYANGKARI 1 KABUPATEN KUBU RAYA - Uswatun Hasanah; Syambasril Syambasril; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research is motivated by the curiosity of the researcher toward the learning process of anecdotal texts in class X MIA I of Kemala Bhayangkari 1 High School, Kubu Raya District. This study aims to describe the planning, implementation, and result of anecdotal text learning to students of X MIA I Kemala Bhayangkari 1 High School, Kubu Raya Regency. The method used in this study is descriptive in form of qualitative research. The data sources of this study were Indonesian language subject taughttostudents of class X MIA I, with number of student was 30 students. The data in this study are in form of planning, implementation, and the results of anecdotal text learning. Data collection techniques are observation, documentation, and interviews. Meanwhile, data collection tools are observedby guidelines, interview guidelines, and recording devices. Data analysis is: data reduction, data presentation, and data inference. The results of learning planning research still have weaknesses, namely the teacher does not include an attitude assessment. learning implementation activities consist of preliminary, core and concluding activities; there is a discrepancy between the lesson plan designed by the teacher in classroom learning. Learning outcomes obtained by students on average students have reached the KKM score.  Keywords:Anecdotal Text, Teaching Learning, 2013 Curriculum